MeABL5, an ABA Insensitive 5-Like Basic Leucine Zipper Transcription Factor, Positively Regulates MeCWINV3 in Cassava (Manihot esculenta Crantz) - Liu, Jiao; Chen, Xia; Wang, Shuo; Wang, Yuanyuan; Ouyang, Yujun; Yao, Yuan; Li, Ruimei; Fu, Shaoping; Hu, Xinwen; Guo, Jianchun (Frontiers in Plant Science, 2019)
The basic leucine zipper (bZIP) transcription factor family plays crucial roles in multiple biological processes, especially stress responses. Cassava (Manihot esculenta Crantz) is an important tropical crop with a strong tolerance to environmental stresses such as drought, heat, and low-fertility environments. Currently, limited information is available regarding the functional identification of bZIP transcription factors in response to abiotic stress in cassava. Herein, a gene encoding an ABA Insensitive 5 (ABI5)-like transcription factor, designated as MeABL5, was identified in cassava. Sequence and phylogenetic analysis showed that MeABL5 is a cassava bZIP transcription factor that is not included in the previously identified cassava bZIP family members, belongs to subfamily A, and has high sequence similarity to ABI5-like proteins. Subcellular localization and transactivation assays revealed that MeABL5 was a nuclear-localized protein and possessed transactivation activity. Furthermore, MeABL5 was able to specifically interact with the ABRE cis-element in the promoter of the cassava major cell wall invertase gene, MeCWINV3, in vitro and in vivo. MeABL5 and MeCWINV3 exhibited similar expression patterns in various organs or tissues and under abiotic stress in cassava. The expressions of MeABL5 and MeCWINV3 within cassava plantlets were both induced by exogenous abscisic acid (ABA), gibberellic acid (GA3), methyl jasmonate (MeJA), and heat. Overexpression of MeABL5 increased the activity of the MeCWINV3 gene, and the up-regulated expressions of MeCWINV3 were significantly activated under ABA-, salicylic acid (SA)-, and MeJA-induced conditions. Overall, these results suggest that MeABL5 is a positive regulator of MeCWINV3 and might participate in the robust resistance of cassava in response to abiotic stress. This study also provides a foundation for further research on ABA-mediated and stress-related signaling pathways in cassava.